Where are the enslaved?: TripAdvisor and the narrative landscapes of southern plantation museums. Issue 3 (2nd July 2016) - Carter, Perry L.
ABSTRACT: This study examines two southern Louisiana plantation museums: Laura and Oak Alley, using a framework that stresses the narrative power and politics of these heritage sites. Located a mile from each other along the Mississippi River, they present two similar yet different narratives of the antebellum American South. Laura places more emphasis on the enslaved who inhabited the plantation than does Oak Alley, whose narrative centers upon the opulence of the plantation home – that is, 'the big house'. This study explores what visitors take away from their plantation tours. Specifically, it examines their thoughts about how the enslaved are represented at these two museums. The study's data come from visitors' comments posted on the travel website TripAdvisor. The object of the study is to gain a greater understanding of what visitors learn about the history of the enslaved on these tours and how they participate, along with site managers, in the narrative construction of the plantation and negotiating the divide between tourism as amusement and tourism as memorial.